SAR exploration at the C-3 position of tetrahydro-β-carboline sstr3 antagonists. Issue 6 (15th March 2016) - He, Shuwen; Dobbelaar, Peter H.; Guo, Liangqin; Ye, Zhixiong; Liu, Jian; Jian, Tianying; Truong, Quang; Shah, Shrenik K.; Du, Wu; Qi, Hongbo; Bakshi, Raman K.; Hong, Qingmei; et al.
Graphical abstract: MK-4256, a tetrahydro-β-carboline sstr3 antagonist, was discontinued due to a cardiovascular (CV) adverse effect observed in dogs. Additional investigations revealed that the CV liability (QTc prolongation) was caused by the hERG off-target activity of MK-4256 and was not due to sstr3 antagonism. In this Letter, we describe our extensive SAR effort at the C3 position of the tetrahydro-β-carboline structure. This effort resulted in identification of 5-fluoro-pyridin-2-yl as the optimal substituent on the imidazole ring to balance sstr3 activity and hERG off-target liability. Abstract: MK-4256, a tetrahydro-β-carboline sstr3 antagonist, was discontinued due to a cardiovascular (CV) adverse effect observed in dogs. Additional investigations revealed that the CV liability (QTc prolongation) was caused by the hERG off-target activity of MK-4256 and was not due to sstr3 antagonism. In this Letter, we describe our extensive SAR effort at the C3 position of the tetrahydro-β-carboline structure. This effort resulted in identification of 5-fluoro-pyridin-2-yl as the optimal substituent on the imidazole ring to balance sstr3 activity and the hERG off-target liability.